Effectiveness of Acceptance and Commitment Therapy on Pain Catastrophizing, Pain Self-Efficacy, and Psychological Flexibility in Individuals with Chronic Pain: A Quasi-Experimental Study - Fatemeh Moqbeli; Fateme Mohebi Rezaei; Elnaz Seyyedbaglou; Parisa Fatahi; Javad Adeldoust; Mohammad Amin Roustaei Hossein Abad (Health Nexus, 2026)
Background: Chronic pain is a persistent biopsychosocial condition in which pain-related thoughts, behavioral avoidance, emotional distress, and perceived coping ability can interact to maintain disability and suffering. Acceptance and Commitment Therapy (ACT) is designed to increase psychological flexibility and help individuals engage in valued action even when pain and distress are present. Objective: This study examined the effectiveness of ACT on pain catastrophizing, pain self-efficacy, and psychological flexibility in adults with chronic pain. Methods: A quasi-experimental pretest-posttest control group design with a two-month follow-up was used. Thirty adults with chronic pain were recruited through online platforms and purposively selected according to eligibility criteria. Participants were randomly assigned to an ACT group (n = 15) or a control group (n = 15). The ACT group received eight weekly 90-minute online group sessions, whereas the control group received no intervention during the active study period. Measures included the Pain Catastrophizing Scale, Pain Self-Efficacy Questionnaire, and Acceptance and Action Questionnaire-II. Data were analyzed using repeated-measures ANOVA and Bonferroni comparisons. Results: The ACT group showed marked improvement from pretest to posttest and follow-up. Pain catastrophizing decreased from 37.80 to 26.07 at posttest and 26.80 at follow-up. Pain self-efficacy increased from 30.40 to 42.27 at posttest and 43.47 at follow-up. Psychological flexibility improved as AAQ-II scores decreased from 31.33 to 19.80 at posttest and 19.20 at follow-up. Significant time, group, and time by group effects were reported for all outcomes. Conclusion: ACT was associated with sustained reductions in pain catastrophizing and improvements in pain self-efficacy and psychological flexibility among individuals with chronic pain. Larger randomized trials with active controls and longer follow-up periods are recommended.